Analysis of Alzheimer Disease Plasma Biomarker pTau‐181 in Individuals of Diverse Admixed Ancestral Backgrounds. (20th December 2022) - Grimmer, Timo; Rajabli, Farid; Garcia‐Serje, Catherine; Arvizu, Jamie; Larkin‐Gero, Emma; Whitehead, Patrice L.; Hamilton‐Nelson, Kara L.; Adams, Larry D.; Contreras, Maricarmen; Sanchez, Jose Javier; Tejada, Sergio; Mena, Pedro Ramon; et al.
Abstract: Background: Plasma proteins, including phosphorylated threonine‐181 of Tau (pTau181) are used as biomarkers for differential diagnosis and preclinical detection of Alzheimer disease (AD). However, observation and measurement of these biomarkers are mostly from individuals of non‐Hispanic, European ancestry. Given differences in AD risk, generalizability of these findings is not assured in individuals of diverse ancestry. This study evaluates the utility of plasma pTau181 in discriminating clinically diagnosed AD from cognitively intact, age‐matched controls in ancestrally diverse, admixed cohorts. Method: We measured pTau181 with Simoa chemistry using the pTau181 AdvantageV2 on the Quanterix HD‐X. Our cohorts consisted of 642 African Americans (162 AD and 480 controls), 906 Puerto Ricans (385 AD and 521 controls), 149 Peruvians (49 AD and 100 controls), 60 Cubans (26 AD and 34 controls), 246 individuals of non‐Hispanic, European ancestry (22 AD and 224 controls), and 58 autopsy confirmed AD cases of European ancestry with plasma isolated from EDTA blood tubes. Samples were randomized, measurements performed in duplicate, and non‐parametric Kruskal‐Wallis tests used to detect differences in biomarker concentrations between cases and controls in each cohort. Result: Median pTau levels in cases was higher than controls in all cohorts assayed: African Americans (2.30±1.14pg/mL vs 1.15±2.99pg/mL, pcorr =2.0x10 ‐27 ); Puerto Ricans (2.33±1.82pg/mL vs 1.44±1.21pg/mL, pcorr =8.2x10 ‐32 ); Peruvians (2.63±1.64pg/mL vs 2.13±1.42pg/mL, pcorr =0.02); Cubans (2.09±1.16pg/mL vs 1.35±0.67pg/mL, pcorr =0.02); and European ancestry (2.40pg/mL±0.78pg/mL vs 1.54pg/mL ±1.44pg/mL, pcorr =0.02). The pTau levels in the autopsy confirmed cases (2.96±2.29 pg/mL) were not significantly higher than AD cases in the other ancestries. Conclusion: This study suggests pTau181 as a biomarker is generalizable across genetic ancestries, though potential sex and age effects remain to be determined. Ultimately, combining genomic and biomarker data, including pTau181 and other AD related plasma biomarkers such as Aβ40 and Aβ42, from diverse individuals will increase understanding of genetic risk and refine clinical diagnoses in individuals of diverse ancestries.